ФЕНОМЕН NO-REFLOW: МОЖЛИВОСТІ КОНТРАСТНОЇ ЕХОКГ- ДІАГНОСТИКИ - Середюк, Н.М.; Фреїк, С.П.; Бєлінський, М.В.; Матлах, А.Я.; Королюк, В.Д. (Українські медичні вісті, 2023)
ФЕНОМЕН NO-REFLOW: МОЖЛИВОСТІ КОНТРАСТНОЇ ЕХОКГ-ДІАГНОСТИКИ